2021
DOI: 10.1002/eji.202049141
|View full text |Cite
|
Sign up to set email alerts
|

Human myeloid‐derived suppressor cell expansion during sepsis is revealed by unsupervised clustering of flow cytometric data

Abstract: Myeloid‐derived suppressor cells (MDSCs) are important regulators of immune processes during sepsis in mice. However, confirming these observations in humans has been challenging due to the lack of defined preparation protocols and phenotyping schemes for MDSC subsets. Thus, it remains unclear how MDSCs are involved in acute sepsis and whether they have a role in the long‐term complications seen in survivors. Here, we combined comprehensive flow cytometry phenotyping with unsupervised clustering using self‐org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Although it is known that circulating neutrophils and other mature PMNs are post-mitotic, we believe that these cells might be retaining a G2/M-like transcriptional profile as a result of an increased proliferation of myelocytes and pre-neutrophils in the bone marrow ( 35 ). Consistently with this hypothesis, we and others have shown that sepsis patients exhibit a higher proportion of immature PMN-myeloid-derived suppressor cells compared to healthy donors ( 36 , 37 ). Similarly, a recent study identified a population of proliferative neutrophil precursors in the spleen of healthy mice, suggesting that such progenitors can egress the bone marrow while retaining their ability to proliferate ( 38 ).…”
Section: Discussionsupporting
confidence: 88%
“…Although it is known that circulating neutrophils and other mature PMNs are post-mitotic, we believe that these cells might be retaining a G2/M-like transcriptional profile as a result of an increased proliferation of myelocytes and pre-neutrophils in the bone marrow ( 35 ). Consistently with this hypothesis, we and others have shown that sepsis patients exhibit a higher proportion of immature PMN-myeloid-derived suppressor cells compared to healthy donors ( 36 , 37 ). Similarly, a recent study identified a population of proliferative neutrophil precursors in the spleen of healthy mice, suggesting that such progenitors can egress the bone marrow while retaining their ability to proliferate ( 38 ).…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that either an association with mortality was missed because of sample size, or that the absence of association was genuine. In line with the second option, a recent study failed to detect an association between mortality and the expansion of PMN-MDSCs in blood sampled from sepsis patients at ICU admission and 3 days later [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that sepsis per se can result in the substantial augmentation of MDSCs in peripheral blood, representing one of the hallmarks of immunosuppressive response. Both circulating G-MDSCs and M-MDSCs were noted with significant increases at the early stage of sepsis, which were defined as CD14 - CD15 + and CD14 + CD15 - HLA-DR –/low , respectively ( 114 ). Nevertheless, G-MDSCs were reported to be more sensitive in discriminating septic and non-septic patients than M-MDSCs did ( 39 ).…”
Section: Monitoring the Alterations Of The Innate Immune Systemmentioning
confidence: 99%